2014
DOI: 10.7241/ourd.20141.04
|View full text |Cite
|
Sign up to set email alerts
|

Association between Herpes Simplex virus type 2 (HSV 2) and bad obstetric outcomes

Abstract: Introduction: HSV is a common human pathogen that lead to lifelong latent infection. Maternal infections may be associate with transmission to the fetus. The risk factors associated with HSV 2 seropositivity in pregnant women in Iraq are not well studied. Aim: The present study conducted to verify the prevalence of HSV 2 infections in women with bad obstetric history (BOH) in Kirkuk Governorate. Material and Methods: HSV 2 seropositivity among women aged 14 to 48 years was investigated by determination of HSV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
(78 reference statements)
1
5
0
Order By: Relevance
“…The variation may be due to differences in sexual behavior or socio-demographic characteristics of the study population [17]. On the other hand, the lower prevalence was also reported in similar studies [8, 14,23]. This can be supported by the fact that HIV-1 infected individuals were more exposed to HSV-2 than other populations [22].…”
Section: Discussionsupporting
confidence: 65%
“…The variation may be due to differences in sexual behavior or socio-demographic characteristics of the study population [17]. On the other hand, the lower prevalence was also reported in similar studies [8, 14,23]. This can be supported by the fact that HIV-1 infected individuals were more exposed to HSV-2 than other populations [22].…”
Section: Discussionsupporting
confidence: 65%
“…This finding similar to some studies. 21,41,42 While other studies found increases in the infection with the level of education by (17), studies show high seroprevalence increased with education women. 10 However, 3,14,23 found no significant between education level and HSV-2 seropositivity.…”
Section: Discussionmentioning
confidence: 93%
“…25 The seroprevalence of HSV-2 IgG was found statistically significantly associated with the occupation of the mother. 14,17,42 However, 21,23,43 found no significant between occupation and HSV-2 seropositivity.…”
Section: Discussionmentioning
confidence: 94%
“…Infections are implicated as an important cause of bad pregnancy outcomes [3,4]. Recent studies in Iraq suggest that Toxoplasma gondi, Cytomegalovirus, Rubella virus, and Herpes Simplex Virus infections were with positive association with BOH [5][6][7][8][9][10][11][12][13][14]. In addition, abnormal immunological responses may play a role in the pathogenesis of bad pregnancy outcomes [15,16].…”
Section: Introductionmentioning
confidence: 99%